Arbitral Awards of the Cairo Regional Centre for International Commercial Arbitration - Alamedin, Mohiedin Ismail (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
The Arbitral Awards of the Cairo Regional Centre for International Commercial Arbitration addresses many significant issues and questions, including the following: * Do rules of limitation have a role in arbitration? * How greatly do administrative contracts differ from civil contracts in the closing years of this century? * Obtaing permissions of works - is this the task of the employer or the contractor? * What can the arbitrator do if several exchange rates apply to the consideration of a contract? It is expected that by the end of 1999 the number of international arbitration cases registered with the Centre will have reached 200. While individual CRCICA awards have occasionally been published, there has never been an independent compilation of all the awards issued by the Centre. This important new volume contains a collection of arbitral awards made up to 1996, with those made originally in Arabic translated into English. The editors have summarised each award and included commentary where appropriate, and the awards are followed by legislative or statutory articles as relevant.